Analisis Literatur tentang Integrasi Kecerdasan Buatan dalam Perekrutan: Implikasi bagi Manajemen SDM - Juniar, Andi Maghfirah; Citta, Andi Batary (PT Maju Malaqbi Makkarana, 2024)
This study aims to analyze the integration of artificial intelligence (AI) in the employee recruitment process and its implications for human resource management (HR). This study uses a qualitative approach based on literature analysis to explore the potential of AI in improving recruitment efficiency and accuracy, while identifying challenges such as algorithmic bias, lack of transparency, and threats to candidate data privacy. The results show that AI can automate various recruitment processes, including candidate screening and evaluation, which significantly saves time and costs. However, the potential for algorithmic bias caused by non-inclusive training data is one of the main obstacles to the fair and ethical implementation of AI. In addition, supportive regulations and policies, such as the Personal Data Protection Law (UU PDP) in Indonesia, play an important role in ensuring the responsible use of AI. These regulations must include personal data protection, transparency, and bias mitigation in AI-based decision making. This study concludes that while AI has great potential to revolutionize recruitment, its implementation requires a careful and strategic approach. Further research is recommended to focus on empirical studies in various organizational contexts, the development of inclusive algorithms, and their impact on candidate experience, in order to create a more holistic and sustainable recruitment system.